Peningkatan Hasil Belajar Pada Kemampuan Menulis Permulaan Melalui Media Puzzle Peserta Didik Kelas II SD Negeri Trukan - Utaminingtyas, Siwi; Utami, Wulan Tri Puji; Mahardika, Agitta (Universitas Muhammadiyah Magelang, 2023)
The purpose of this study was to determine the increase in learning outcomes in students' initial writing skills in Indonesian language learning class II elementary school with puzzle media. The research method uses Classroom Action Research with the implementation of 2 cycles. The research was conducted in SD Negeri Trukan Class II with a total of 18 students consisting of 5 boys and 13 girls. This study uses test and non-test collection techniques. The research instruments used were multiple choice questions and observation sheets. The data analysis technique used was in the form of quantitative techniques obtained from student test results and qualitative techniques obtained from observation sheets of teacher and student activities. The results showed that there was an increase in the learning outcomes of students' writing abilities in the first cycle with a completeness of 52.9% and in the second cycle it reached 82.3% completeness. It can be concluded that the use of puzzle media in learning Indonesian can improve initial writing skills in grade II elementary school.